A. Muñoz y G. Martino (2019). Historia mínima del yoga. México: El Colegio de México. 293 pp. - Larios Robles, Vanessa (Estudios de Asia y África, 2020)
A. Muñoz y G. Martino (2019). Historia mínima del yoga. México: El Colegio de México. 293 pp.